Climate care is health care: A call for collaborative pharmacy action. Issue 5 (21st February 2021) - Gahbauer, Alice; Gruenberg, Katherine; Forrester, Catherine; Saba, Amir; Schauer, Samuel; Fravel, Michelle; Lam, Ashley; Brock, Tina
Abstract: Climate change and ecosystem degradation threaten human health and exacerbate pre‐existing social determinants of health. The prescription drug sector accounts for a significant portion of health care system contributions to greenhouse gas and waste production. Pharmacists are therefore well‐positioned to transform health care toward environmentally sustainable models; however, additional pharmacist education on climate mitigation and sustainable practice is needed. A team of practicing pharmacists and pharmacy students from the United States and Australia aimed to define pharmacists' roles in environmental stewardship by evaluating pre‐existing pharmacy‐led efforts in reducing waste, greenhouse gas emissions, and other health care‐associated environmental impacts. We also describe opportunities for education in pharmacist training as a means to enhance the profession's capacity for environmentally sustainable health care practice and leadership. Information on specific drugs' ecological footprints is increasingly available; pharmacists, as drug information experts, can incorporate sustainability considerations into their drug procurement and prescribing recommendations. Pharmacists also play a critical role in public education about environmentally responsible drug disposal. Finally, we suggest collaborative steps that U.S. organizations involved in pharmacy education could take to ensure that future "practice readiness" includes competence in sustainable health care practices.